Novel approach for strengthening lightweight foamed concrete with textile carbon grid laminates / Anisah Mat Serudin and Md Azree Othuman Mydin - Mat Serudin, Anisah; Othuman Mydin, Md Azree (2018)
People in the construction industry around the world have acknowledged the future need for construction materials that are low in self-weight, long-lasting, simple to construct, cost-friendly and yet more environmentally sustainable. One of the suggestions in the frontline has been the finding, developing and utilizing of alternative, non-conventional building materials including the potential use of lightweight foamed concrete. Lightweight foamed concrete which is produced with Portland cement is noble in compression but fragile in tension because it comprises various micro pores that tend to crack. Hence this research project explored the potential use of textile carbon grid laminates with reinforced lightweight foamed concrete. One of the major problems faced in reinforced lightweight concrete construction is the corrosion of reinforcing steel which ominously distresses the lifespan and robustness of concrete assemblies. Hence, textile carbon grid laminates as a replacement to welded wire mesh can commendably abolish the delinquent of decomposition as they are protected from corrosion. Three densities of lightweight foamed concrete of 800kg/m3 , 1100kg/m3 and 1400kg/m3 will be cast and tested with 3 different types of textile carbon grid laminates which are 130g, 145g and 160g (weight per square meter). The parameters that will be evaluated are compressive strength, flexural strength, splitting tensile strength, scanning electron microscopy, performance index and failure modes. The results obtained showed that the incorporation of textile carbon grid laminates had improved the flexural strength, compressive strength and splitting strength of lightweight foamed concrete. When the basis weight of textile carbon grid laminates increases (from 130g to 160g), the greater the tensile bond strength of lightweight foamed concrete. As the load increases on the lightweight foamed concrete, a flew in the matrix may spread over the specimen cross-section